Duckweed-derived magnetic adsorbent for efficient removal of methylene blue - Seng, Kelly Wong Kai; Zheng, Alvin Lim Teik; Jeffrey, Karen Bulan; Hii, Tan Toh; Chung, Eric Lim Teik; Lease, Jacqueline; Andou, Yoshito (Springer Science and Business Media Deutschland GmbH, 2026)
Low-cost and easily recoverable adsorbents are urgently needed for efficient treatment of dye-contaminated wastewater. In this study, a green magnetic duckweed-derived adsorbent (MDW) was synthesized via co-precipitation of Fe3O4 nanoparticles (NPs) onto dried duckweed using ascorbic acid (AA) as a reducing agent. The MDW exhibited a maximum methylene blue (MB) adsorption capacity of 78.59 mg/g under optimal conditions of pH 10, 50 mg/L initial MB concentration, 10 mg adsorbent dosage, and 60 min contact time, achieving a removal efficiency of 85.27%. Kinetic analysis showed that adsorption followed the pseudo-second-order (PSO) model (R² > 0.999), while equilibrium data were best described by the Temkin isotherm model, indicating heterogeneous surface interactions. Thermodynamic analysis revealed an exothermic and spontaneous process with negative ΔG° values across the temperature range of 298–318 K. The MDW retained over 69% of its initial removal efficiency after five regeneration cycles, confirming good reusability. Cost analysis estimated the synthesis cost at approximately RM 29.51/kg, highlighting economic feasibility. These findings demonstrate that MDW is a sustainable, low-cost, and magnetically recoverable adsorbent with strong potential for scalable wastewater treatment applications.